The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5812/compreped.82630
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Home Phototherapy in Neonatal Jaundice

Abstract: Background: Jaundice is one of the most common problems in the neonatal period. Phototherapy is one of the most commonly used treatments for jaundice that can be used as a simple, practical home-based treatment. Hospitalization during the first days of birth to conduct phototherapy may result in problems like nosocomial infections and mother separation from the baby. Objectives: The aim of this study was to evaluate the efficacy of home phototherapy in the duration of treatment, mean bilirubin level, and compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…The current study revealed that there was gradual decrease in bilirubin level as the mean difference of the TSB at admission was (16.58± 1.31) and at discharge was (8.76± 0.67) with highly statistically significant difference, however; there was no statistically significant differences in the mean value of the DSB on admission and at discharge (P=0.179). This is agreed to some extent with a recent study in 2019 that revealed that bilirubin level was (16.46 ± 1.47) in the first day (at admission) and (10.08 ± 1.07) at the third day (Sardari et al, 2019).…”
Section: Mazary Et Al 2017)supporting
confidence: 93%
See 1 more Smart Citation
“…The current study revealed that there was gradual decrease in bilirubin level as the mean difference of the TSB at admission was (16.58± 1.31) and at discharge was (8.76± 0.67) with highly statistically significant difference, however; there was no statistically significant differences in the mean value of the DSB on admission and at discharge (P=0.179). This is agreed to some extent with a recent study in 2019 that revealed that bilirubin level was (16.46 ± 1.47) in the first day (at admission) and (10.08 ± 1.07) at the third day (Sardari et al, 2019).…”
Section: Mazary Et Al 2017)supporting
confidence: 93%
“…As regards the duration of phototherapy, the current study came in agreement with Sardari et al, (2019) that revealed that the mean duration of phototherapy in their study was 48 hours. Regarding the side effects of phototherapy, the current study revealed that the most common complication was skin rash, which developed in about 4% of cases only.…”
Section: Mazary Et Al 2017)supporting
confidence: 90%
“…[8,9] Home phototherapy for hyperbilirubinemia has been found to be effective in some high-income countries when conducted under the supervision of nurses. [10][11][12] In Bangladesh, several studies showed the effectiveness of a home-based community health worker (CHW) approach in delivering maternal and newborn health interventions including message delivery for health promotion, identi cation of sick newborns, hospital referral as well as home treatment of newborn sepsis. [13][14][15][16][17] In Bangladesh and other LMICs around the world, CHWs have successfully implemented home-based diabetes management, postnatal newborn care, maternal and child nutrition, and child development interventions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 12 13 14 ] For instance, Sardari et al . [ 15 ] revealed that at-home phototherapy can be a suitable alternative to the treatment of neonatal jaundice, reducing parental stress and preventing hospitalization of infants. [ 16 ] Some researchers designed home-care programs for a number of children with physical disabilities and chronic conditions and their families through several studies.…”
Section: Introductionmentioning
confidence: 99%